Determinar la aplicación de la estrategia AIEPI en el componente de enfermedad diarreica aguda en los niños que acuden a Consulta Externa del Hospital Universitario de Motupe, en el periodo febrero - agosto del 2013. - Tenesaca Guamán, Cristian Fernando (2013)
The AIEPI strategy developed by O.M.S. and UNICEF, has standardized the attention of the most common health problems, such as diarrhea, to reduce child mortality, generating prevention, care, and treatment and monitoring of patients under 5 years. These researches is a descriptive, prospective, and quantitative and cross in order to determine the application of the AIEPI strategy in children under five with diarrheal illness, assessing gender, age, symptoms, signs, dehydration and hydration plan in a sample of 60 patients attending outpatient Motupe Hospital, from February to August 2013. In 75% of patients with EDA were not treated with AIPE strategy, there is a predominance of the female by 58%, the highest proportion age between 1 month - 1year with 30%, 100% is manifested with diarrhea, 92% have no dehydration and hydration is Plan A by 92%. There was not implementing the IMCI strategy in EDA, in patients attending hospital outpatient Motupe. Keywords: AIEPI DIARRHEA HYDRATION